Pharmaco-toxicological aspects of thymol in veterinary medicine. A systematic review - Pérez Gaudio, Denisa; Giantin, Mery; Pauletto, Marianna; Dacasto, Mauro (Frontiers in Veterinary Science, 2025)
IntroductionThymol, a phenolic compound present in essential oils, has shown promising pharmacological properties and potential veterinary applications. This systematic review aims to evaluate the pharmacological and toxicological effects of thymol on animals.Materials and methodsA comprehensive search following PRISMA 2020 guidelines was conducted across databases including PubMed, Scopus, Google Scholar, Web of Science, and LILACS. Various health descriptors, medical subject headings terms, and their synonyms were used to identify studies examining thymol's effects in animals, including its in vitro, in vivo, and in silico toxicity, as well as its possible environmental impact. Only relevant experimental studies from the last 12 years were included, provided they assessed thymol itself, one of its primary phytoadditive sources, or a blend where thymol was at least as concentrated as other components. The protocol was registered in Open Science Framework (DOI: https://doi.org/10.17605/OSF.IO/B6SF9).ResultsA total of 1.472 records were identified, with 176 meeting inclusion criteria. Studies spanned from 2012 to 2024, indicating that thymol exhibits antimicrobial, antiviral, antifungal, antiparasitic, anti-inflammatory, and antioxidant properties, among others. However, thymol displays dose-dependent toxicity, especially at high levels, affecting mainly the liver and kidneys.DiscussionThymol holds substantial potential as a therapeutic agent in veterinary medicine due to its beneficial effects and relatively low toxicity. Nonetheless, further research is needed to establish safe and effective dosages across different animal species.Systematic review registrationhttps://doi.org/10.17605/OSF.IO/B6SF9.